Effect of combined aerobic exercise and resistance training on postmenopausal women with type 2 diabetes: a systematic review and meta-analysis - Vitor Engracia Valenti; André dos Santos Chagas; Peter Chedraui; Ingrid Soares de Souza; Andrey Alves Porto; Isabel Cristina Esposito Sorpreso; Jose Maria Soares Júnior; Juliana Zangirolami-Raimundo; David M. Garner; Rodrigo Daminello Raimundo (Gynecological Endocrinology)
Background There is no strong evidence demonstrating whether or not aerobic exercise in conjunction with resistance exercise improves metabolic diabetes markers in postmenopausal women.Objective To evaluate the effect of aerobic exercise and resistance training on metabolic markers in postmenopausal women with type 2 diabetes mellitus (T2DM) by means of a systematic review and meta-analysis.Methods The searches were completed using EMBASE, MEDLINE/PubMed, Scopus and Web of Science databases. This study included non-blinded, single or double-blinded randomized control trials and postmenopausal women diagnosed with T2DM. The imposed intervention was aerobic exercise plus any training protocol to strengthen muscle groups for resistance intervention. The outcomes of interest were the blood glucose levels, insulin secretion, homeostasis model assessment-insulin resistance index (HOMA-IR) and glycated hemoglobin (HbA1c). Risk of Bias tools and GRADE were obligatory.Results Three studies were included (83 participants). Exercise intervention ranged between two to four days per week. Compared to the control group, in the group submitted to aerobic exercise + resistance training, no significant change was noted for HbA1c (subtotal = mean difference − 0.35 [95% CI: −0.85, 0.15], p = .17, and heterogeneity = 0%) (GRADE: very low), nevertheless, HOMA-IR index was significantly improved (subtotal = mean difference −0.52 [95% CI: −0.99, −0.05], p = .03, and heterogeneity = 0%) (GRADE: very low).Conclusion Despite the very low certainty found in the quality of evidences, our analysis showed that aerobic exercise along with strength exercise seems to improve some metabolic diabetes markers in postmenopausal women with T2DM. There is a need for further studies to support our preliminary findings.